2000
DOI: 10.1046/j.1523-1755.2000.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Location of mutations within the PKD2 gene influences clinical outcome

Abstract: The identification of groups of mutations in the PKD2 gene, which differ significantly with respect to clinical outcome, is to our knowledge the first description of a genotype/phenotype correlation in autosomal dominant polycystic kidney disease. It also provides evidence against complete loss of function of the mutant PKD2 gene product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 37 publications
1
39
1
1
Order By: Relevance
“…This is consistent with the finding of significant renal disease variability within families with PKD1-linkage (38) and among patients with the same PKD1 mutations (16). Taken together, these data suggest the existence of a modifier effect for AD-PKD (17,38,39). Recent studies have shown that the phenotypic variability of a number of Mendelian disorders is in fact complex because of the existence and interaction of genetic and environmental modifiers (40).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is consistent with the finding of significant renal disease variability within families with PKD1-linkage (38) and among patients with the same PKD1 mutations (16). Taken together, these data suggest the existence of a modifier effect for AD-PKD (17,38,39). Recent studies have shown that the phenotypic variability of a number of Mendelian disorders is in fact complex because of the existence and interaction of genetic and environmental modifiers (40).…”
Section: Discussionsupporting
confidence: 88%
“…However, considerable renal disease variability (age range of onset of ESRD, 40 to 88 yr) was also evident between individual patients. described (17)(18)(19)(20)(21)(22)(23)(24)(25), and the remaining mutations from 21 families are reported here for the first time. The diagnosis of ADPKD in the patients and at-risk individuals from each study family was established using well-established ultrasound-based criteria (26).…”
Section: Study Patientsmentioning
confidence: 96%
See 2 more Smart Citations
“…Significant interfamilial phenotypic differences have been described, and clinically mild PKD1 families documented (22)(23)(24). Furthermore, it has been suggested that the location of the PKD2 mutation influences the clinical outcome (25). An anecdotal association of a specific mutation in three families with early onset disease and/or associated vascular complications has also been reported (26).…”
mentioning
confidence: 99%